Phylogeny, Age, and Evolution of Tribe Lilieae (Liliaceae) Based on Whole Plastid Genomes - Li, Juan; Cai, Jing; Qin, Huan-Huan; Price, Megan; Zhang, Zhen; Yu, Yan; Xie, Deng-Feng; He, Xing-Jin; Zhou, Song-Dong; Gao, Xin-Fen (Frontiers in Plant Science, 2022)
Tribe Lilieae, encompassing Lilium, Notholirion, Cardiocrinum, and Fritillaria, includes economically important crops with horticultural and medicinal value. It is considered to be a core lineage of Liliaceae, but phylogenetic relationships within it, and the timing of origin of individual clades, remain incompletely resolved. To address these issues, we reconstructed the evolutionary history of the tribe. We sequenced 45 Liliaceae plastomes and combined them with publicly available data (for a total of 139 plastomes) to explore the systematics, origin, divergence, and evolution of Lilieae. Our taxon sampling covers all ten sections of Lilium, all Cardiocrinum species, three Notholirion species, and major phylogenetic clades of Fritillaria. Our phylogenetic analysis confirm the monophyly of major sections/subgenera of Lilium and Fritillaria with strong support. We dated the origin of Lilieae to the Eocene, with genera and species radiations inferred to have occurred in the Miocene. The ancestral area reconstruction implies that Lilieae may have originated from the Qinghai Tibet Plateau (QTP): the Himalayas and Hengduan Mountains and uplifting of the QTP likely promoted divergence within the tribe. Ancestral-state reconstructions of bulb component number (including bulblets and scales) show a strong correlation with genus-level phylogenetic diversity in Lilieae. They also predict that the most recent common ancestor of Lilieae had bulbs with numerous bulblets. Based on these observations, we predict that climatic oscillations associated with the QTP uplift played an important role in Lilieae bulb evolution. Our findings provide a well-supported picture of evolutionary relationships and a useful framework for understanding the pathway of bulb evolution within Lilieae, contributing to a better understanding of the evolutionary history of lilies.